Facile Fabrication of ZnO-Nanorods-Array Superhydrophobic Film Modified with Stearic Acid - Wang, Yanfen; Li, Benxia; Xu, Chuyang (Asian Journal of Chemistry, 2012)
Biomimetic superhydrophobic surfaces are attracting more and more research attention due to their potential application as self-cleaning materials. However, the complicated procedure, high cost and instability of most superhydrophobic surfaces significantly limited their applications. In this work, we report a convenient one-step route to obtain a large scale of ZnO-nanorods-array film on zinc plate substrate. After the modification of hydrophobic stearic acid, the film displays a remarkable superhydrophobic property with a contact angle higher than 150º. The wettability of surfaces can be adjusted and controlled by changing the content of stearic acid.